Immune involvement of the contralateral hemisphere in a glioblastoma mouse model - Matheus H W Crommentuijn; Sjoerd T T Schetters; Sophie A Dusoswa; Laura J W Kruijssen; Juan J Garcia-Vallejo; Yvette van Kooyk (Journal for ImmunoTherapy of Cancer)
Background Glioblastoma (GBM) is the most common and deadliest form of brain cancer in adults. Standard treatment, consisting of surgery and radiochemotherapy, only provides a modest survival benefit and is incapable of combating infiltrating GBM cells in other parts of the brain. New therapies in clinical trials, such as anti-programmed cell death 1 immunotherapy, have so far shown limited success in GBM. Moreover, it is unclear how the growth of GBM suppresses the immune system locally at the site of the brain tumor or if distant sites of tumor cell migration are also involved. Invasive GBM cells in brain tissue beyond the primary tumor limit the use of surgery, thus immunotherapy could be beneficial if activated/suppressed immune cells are present in the contralateral hemisphere.Methods Here, we used a syngeneic orthotopic GL26 GBM mouse model and multiparameter fluorescence-activated cell sorting analysis to study the phenotype of resident and infiltrating immune cells in both the brain tumor hemisphere and contralateral hemisphere.Results We show that lymphoid cells, including tumor antigen-specific CD8+ tumor-infiltrating lymphocytes (TILs) are present in the tumor and are characterized by a tolerogenic phenotype based on high immune checkpoint expression. Massive infiltration of myeloid cells is observed, expressing immune checkpoint ligands, suggesting an immune-dependent coinhibitory axis limiting TIL responses. Surprisingly, these phenotypes are paralleled in the contralateral hemisphere, showing that infiltrating immune cells are also present at distant sites, expressing key immune checkpoints and immune checkpoint ligands.Conclusion Whole-brain analysis indicates active immune involvement throughout the brain, both at the site of the primary tumor and in the contralateral hemisphere. Using the right combination and timing, immune checkpoint blockade could have the potential to activate immune cells at the site of the brain tumor and at distant sites, thereby also targeting diffusely infiltrating GBM cells.